HCG-responsive aldosteronoma with transient secretion during pregnancy confirmed through HCG-stimulated adrenal venous sampling - Castinetti, Frederic; Guerin, Carole; Louiset, Estelle; Lacroix, André (Frontiers in Endocrinology, 2023)
Primary aldosteronism can be regulated by the ectopic expression of G-protein coupled receptors in aldosteronomas or bilateral hyperplasias. We report a rare case of a young woman in whom 2 pregnancies were complicated by pre-eclampsia and 1 miscarriage. The transient primary aldosteronism during pregnancies suggested the possibility of hCG stimulated aberrant adrenal expression of LHCG receptor in her adrenal tissues. This was supported by increased aldosterone and renin suppression during 5-day HCG stimulation test outside of pregnancy. Following a second 5-day HCG stimulation test, bilateral simultaneous adrenal vein sampling identified a lateralized source of aldosterone from an 8 mm right adrenal nodule. A right laparoscopic adrenalectomy resulted in clinical and biochemical cure and allowed a further uneventful pregnancy a few years later. This case illustrates the indication to investigate for potential primary aldosteronism in woman with transient hypertension during pregnancy.